Role of Artificial Intelligence in Business Communication - Balan, Yugeetha (Journal of Contemporary Issues in Media & Communication (JCIMC), 2024)
The integration of Artificial Intelligence (AI) in business communication has revolutionized how organizations interact with customers and manage internal communications. However, this transformation is accompanied by significant ethical and practical challenges, including concerns about data privacy, biases in AI-generated content, and the potential erosion of authentic human interactions. This paper identifies key research gaps in the current understanding of AI's impact on business communication, particularly in addressing the complexities of AI bias, the need for robust oversight mechanisms, and the ethical considerations in preserving human-centric communication. Future research is recommended to focus on developing advanced frameworks for bias detection and mitigation in AI systems, strategies to balance AI efficiency with the maintenance of personal connections, and the creation of genuine corporate social responsibility (CSR) practices that integrate AI ethics deeply into organizational processes. Additionally, exploring the broader implications of AI on the meaningfulness of work is crucial to ensure that AI advancements do not undermine the intrinsic value of human labour. Through addressing these research areas, businesses can better navigate the complexities of AI in communication and foster more ethical, effective, and human-centered organizational practices.